115 An Audit on Dexamethasone Prescribing Practice on Surgically Managed Metastatic Spinal Cord Compression Patients in the Manchester Centre for Clinical Neurosciences: Lessons Learned in Closing the Loop. (4th May 2021) - Laurente, R; Mohammed, R; Elmalky, M
Abstract: Metastatic Spinal Cord Compression is a surgical emergency owing to its propensity to cause significant morbidity and mortality. Dexamethasone is prescribed to reduce oedema and promote vascular membrane stabilization. The is done so until a more definitive management has been performed. This is a retrospective study evaluating the steroid-prescribing practice for MSCC patients in 2018 at a tertiary spinal unit in Greater Manchester. Thirty-three patients who underwent stabilisation were evaluated in terms of both steroid prescribing and weaning practices. Standards used against for both were the NICE guidelines and the Edinburgh/Christie's guidelines. Of the 33 patients evaluated, only 1 patient received the correct loading dose of 16mg, whilst 27 went straight to being given 8mg BD. 5 did not receive dexamethasone at all. In terms of discontinuation/weaning, 26 were weaned accordingly and 2 were not weaned to continue as adjuvant treatment. Dexamethasone prescribing practises has since improved over the past two years. 93% of the patients have been correctly weaned as compared to 38% in the past. In terms of prescription, much needs to be done as almost all the patients evaluated did not get the correct loading dose despite receiving the appropriate maintenance.